Problematika Metode Omnibus Law dalam Pembentukan Peraturan Perundang-Undangan : Analisis terhadap Undang-Undang No. 13 Tahun 2022 dan Urgensi Pembentukan Badan Regulasi Nasional di Indonesia - Fuji Syifa Safari; Satriya Nugraha; Vicka Prama Wulandari; Yolita Elgeriza Agustin; Claudia Yuni Pramita (Prosiding Seminar Nasional Ilmu Hukum, 2024)
The enactment of Law Number 13 of 2022, concerning the Second Amendment to Law Number 12 of 2011 on the Establishment of Legislation, is a follow-up to Constitutional Court Decision No. 91/PUU-XVIII/2020 regarding the formal review of Law Number 11 of 2020 on Job Creation. However, during its formation process, Law Number 13 of 2022 can be considered as not meeting the criteria of an open cumulative law due to the Constitutional Court's decision. It is viewed as a tool to legitimize the flawed legislative process that followed the Court's ruling on Law Number 11 of 2020. The method used in this analysis is normative juridical, applying a statutory approach. The results of this research indicate that the reconstruction of substantive content using the omnibus law method in Law Number 13 of 2022 does not align with regulatory governance in Indonesia, which remains characterized by overlapping regulations—both horizontally and vertically—and is irrelevant to the existing decentralization system. The establishment of a National Regulatory Agency (BRN) is proposed as a constructive solution to ensure that the quality of academic drafts, methods, and regulatory content is thoroughly examined for feasibility, thereby creating a national regulatory system that is high quality, orderly, and optimal.